KEDUDUKAN KREDITOR SEPARATIS DALAM PROSES KEPAILITAN - NOVIE AFIF MAULUDIN (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this study is to find out how the position of separatist creditors in the bankruptcy process is. To answer the problem formulation of the author. The research method used is a normative juridical research method, namely legal research conducted by examining library materials or secondary data. By collecting and then reviewing library materials or secondary data relevant to this research. The results of the research that the provisions in the Law on Guarantees and the Law on Bankruptcy and Debt Payment Delays in which the position of separatist creditors takes precedence over other creditors, and is a separation of creditors' rights, is the author's interpretation of the above discussion, so hereby the author draws conclusions based on the results of the above discussion. . Separatist creditors have the same rights to liquidate assets in the bankruptcy process as if the debtor is not declared bankrupt. However, there are no firm and fast rules between Article 55 paragraph (1) of Law 37/2004 concerning Bankruptcy and Debt Payment Delays and the Civil Code rules regarding the rights of creditors who decide, which can lead to disputes between creditors who decide and practitioners of bankruptcy. In particular Articles 56 and 59 of Law 37/2004 concerning Bankruptcy and Debt Payment Delays. To avoid the above scenario, the bankruptcy practitioner must ensure that the status of the separatist creditor as a lien holder is adequately protected in the settlement of his claim. The transfer of substantive rights by the curator is considered null and void by law, so the provision of Article 56 paragraph (3) of Law 37/2004 concerning Bankruptcy and Debt Payment Delay in the interpretation section needs to be changed. After the substantive rights expire, the guaranteed creditor will compete directly with other creditors